Nominal and Real Wage Rigidities. In Theory and in Europe - Markus Knell (Oesterreichische Nationalbank (OeNB), 2010)
In this paper I study the relation between real wage rigidity (RWR) and nominal price and wage rigidity. I show that in a standard DSGE model RWR is mainly affected by the interaction of the two nominal rigidities and not by other structural parameters. The degree of RWR is, however, considerably influenced by the modelling assumption about the structure of wage contracts (Calvo vs. Taylor) and about other institutional characteristics of wage-setting (clustering of contracts, heterogeneous contract length, indexation). I use survey evidence on price- and wage-setting for 15 European countries to calculate the degrees of RWR implied by the theoretical model. The average levels of RWR are broadly in line with empirical estimates based on macroeconomic data. In order to be able to also match the observed cross-country variation in RWR it is, however, essential to move beyond the country-specific durations of price and wages and to take more institutional details into account.
Keywords: E31; E32; E24; J51; 330; Inflation Persistence; RealWage Rigidity; NominalWage Rigidity; DSGE models; Staggered Contracts